France : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2005)
This 2005 Article IV Consultation highlights that the cyclical recovery of the French economy was interrupted in the first half of 2005, as previously strong domestic demand faltered and the external sector continued to exert a drag on growth. In 2004, growth was faster and more consumption-driven than in other large euro area countries. Employment growth in hours, increases in minimum wages, and some fiscal measures supported private household incomes. The 2006 draft budget targets a reduction in the general government deficit to 2.9 percent of GDP.